Serological survey of Toxoplamosis in South American coatis (Nasua nasua) in Tietê Ecological Park, São Paulo, SP, Brazil - Maia, Jéssica França; Gennari, Solange Maria; Milanelo, Liliane; Furuya, Haroldo Ryoiti; Souza, Vanessa Apafecida Feijó; Vitaliano, Sérgio Netto (Brazilian Journal of Veterinary Research and Animal Science, 2017)
Toxoplasma gondii is an obligate intracellular protozoan parasite that causes toxoplasmosis in humans, domestic animals and wild animals. Although there is serological evidence of T. gondii infection in wild animals, little is known about the role of wildlife in the epidemiological chain of this parasite. The South American coati (Nasua nasua) is an omnivorous species capable of adaptation to different environments. It can be found throughout Brazil, and in anthropized environments it can come into close contact with domestic animals. The present study found occurrences of T. gondii antibodies in South American coatis living in the Tietê Ecological Park, in the municipality of São Paulo, Brazil, through the modified agglutination test (MAT). In total, 99 samples were obtained and 70.70% (n = 70) were positive for anti-T. gondii antibodies, with titers that ranged from 50 to 3200. The data from this study indicate that South American coatis are exposed to this parasite.